PREFERENSI FAKTOR – FAKTOR MOTIVASI KERJA PNS DI DIREKTORAT ZENI ANGKATAN DARAT, JAKARTA - Firman, Galang Nuzul; Lataruva, Eisha (Faculty of Economics and Business Diponegoro University, 2014)
There are 5 motivation factors examined in this study are the factors of leadership,compensation (salary and benefits), the relationship between co-workers, career development, appreciation from organization. The sample in this study is the organization's Civil Service Direktorat Zeni Angkatan Darat, East Jakarta, which amounts to 74 employees. The analysis used in this study is the Spearman Rank Correlation Test, Test of Non - Parametik Mann Whitney and Kruskall Wallis test and Duncan test.The results showed that the preferences of motivational factors in the organization DITZIAD civil servants from the first to the fifth rank is: Leader Factor, Factor Compensation (salary and benefits), the relationship between co-workersfactor, Career Factor, and Factor appreciation. There are five factors correlations significant motivation to work among employees with different gender. There are significant differences between male officers and female officers in assessing the factor of appreciation. Male and female employees alike choose factors as the leader of the main factors that can motivate them to work. Based on class rank, showed significant differences in the career development factors. Employees with the stratification according to rank≥ IIIC preferred career development factors as the most motivating factor, while employees with the stratification according to rank IIIA-IIIB, IIC-IID, IIa-IIb prefer as leader of the main factorsthat motivate them to work.